2016
DOI: 10.1515/anre-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of root canal morphology – a review of the literature

Abstract: The morphological diversity of the inner anatomy of root canals in human permanent teeth is an issue mainly described in endodontics research. In recent years, it is a relatively new point in anthropological studies because it varies by sex, geographic and ethnic circumstances. An unusual number of root canals or their specific systems can differentiate populations around the world. The multiplicity of available methods for detecting root canal systems helps to better understand their complexity; however, most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
4
0
2
Order By: Relevance
“…The majority (70%) of the inhabitants of Myanmar possess Mongoloid traits [ 23 ]. In this study, the prevalence of type IV canal (45.5%) is highest, followed by type I canal (17.8%) and type II canal (17.8%) in the mesiobuccal root, showing the typical Mongoloid trait [ 12 ], whereas Caucasian population shows more type II canal [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority (70%) of the inhabitants of Myanmar possess Mongoloid traits [ 23 ]. In this study, the prevalence of type IV canal (45.5%) is highest, followed by type I canal (17.8%) and type II canal (17.8%) in the mesiobuccal root, showing the typical Mongoloid trait [ 12 ], whereas Caucasian population shows more type II canal [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accurate knowledge of the roots and root canal system of primary teeth can provide a vital source of information for anthropological research, as it is found that both show considerable variation according to geography and ethnicity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…When utilized with a limited field of view (FOV) and small voxel size, it is currently regarded as the “GOLD standard” for determining root canal anatomy. 5 , 7 It is also possible to obtain segments from various levels that do not contain projection errors due to superimposition and magnification, allowing for more precise three-dimensional views of the teeth. 5 …”
Section: Introductionmentioning
confidence: 99%